If it's not what You are looking for type in the equation solver your own equation and let us solve it.
180=(9x-5)+(14x-91)
We move all terms to the left:
180-((9x-5)+(14x-91))=0
We calculate terms in parentheses: -((9x-5)+(14x-91)), so:We get rid of parentheses
(9x-5)+(14x-91)
We get rid of parentheses
9x+14x-5-91
We add all the numbers together, and all the variables
23x-96
Back to the equation:
-(23x-96)
-23x+96+180=0
We add all the numbers together, and all the variables
-23x+276=0
We move all terms containing x to the left, all other terms to the right
-23x=-276
x=-276/-23
x=+12
| 5u+13=108 | | 5n^2+11n-9718=0 | | 4x+18=5x/2 | | 30=4y-14 | | 6•16x-1=90 | | 21=y/3-10 | | 216=36^4-x | | 3m-11=2m+3(2m-2) | | 216=36^2x | | -2n+3(n+1)=5n-17 | | 2n^2+13n-3219=0 | | x^2-15=8 | | -848=16h | | 22b=264 | | 2p=9.42 | | 5x+2x-15=13 | | 7+j=91 | | 2a+6=A-4 | | 7(x+2)10=7x+4 | | 4x-10=7x-31 | | 8x=464 | | 7.2=w/12 | | R=1.03+7.11t-0.38t^2 | | 3x-1/2=60 | | {2^(2n+5)-2^2}÷{2^(n+1)}=4 | | 13(6x+27)+2(x−3)=7 | | 38=5m+3 | | 20−(3x−9)−2=−(−11x+1) | | X^2+12=2x+15 | | 4x/2=21/2 | | 7x+6x=375 | | r+1/2=5.6 |